Orthodontic treatment using miniscrew: Perawatan ortodonti menggunakan miniscrew - Rasdiana Bakri; Eka Erwansyah; Baharuddin M. Ranggang (Makassar Dental Journal, 2023)
Anchorage control is one of the most important-key to obtain successful in clinical orthodontic. Mini-implant orthodontic as known as miniscrew or temporary anchorage devices (TAD) created absolute anchorage. Miniscrew anchorage has greatly ex-panded the limit of clinical orthodontics. Even without patient compliance, miniscrews can provide stationary anchorages for various tooth movements and even make it possible to move the tooth in directions which have been impossible with tradition-al orthodontic mechanics. Orthodontic miniscrew have high mechanical retention with some advantage include adequate anchor-age against uncooperative patient, minimal surgical invasive, allow insertion and removal procedure and no expansion effect re-latively. Application of miniscrew in orthodontic treatment need much attention for some aspects like type and part of mini-screw, indication and contraindication, clinical procedure include insertion and removal of miniscrew moreover unpredict-able complication. Miniscrew is one type of TAD that widely used in orthodontic treatment in providing absolute anchorage